Outcomes of art therapy and coloring for professional and informal caregivers of patients in a radiation oncology unit: A mixed methods pilot study. (October 2019) - Kaimal, Girija; Carroll-Haskins, Katrina; Mensinger, Janell L.; Dieterich-Hartwell, Rebekka M.; Manders, Elizabeth; Levin, William P.
Abstract: Purpose: Caring for cancer patients can be highly stressful for both family caregivers and oncology professionals. These high levels of stress can lead to poorer patient outcomes and increased risk of health problems for the caregivers themselves. Art therapy may help these caregivers as art-making can be a relaxing and enjoyable form of self-expression and art therapists can support individuals in expressing and processing challenging emotions. Research on art-making or art therapy with caregivers of cancer patients has shown some positive results, but its interpretation is limited by the use of multifaceted interventions. Method: In this mixed-methods study we compared two brief arts-based approaches for both professional and informal caregivers: single sessions of coloring or open-studio art therapy, with a 45-minute session each. Assessments imcluded self-reports of affect, stress, self-efficacy, anxiety, burnout arnd creative agency alongside salivary biomarkers before and after the session. Open-ended questions, field notes and observations formed the qualitative part of the study. Results: Thirty-four professional (n=25) and informal (n=9) caregivers participated. Participants in both conditions showed increases in positive affect, creative agency, and self-efficacy and decreases in negative affect, anxiety, perceived stress, and burnout. Participants in both conditions expressed enjoyment, relaxation, appreciation of time away from stressors, creative problem solving, a sense of flow, and personal and existential insight. The two approaches also elicited distinct experiences with participants reporting that they found improved focus in coloring and appreciated the support and freedom of expression in open studio art therapy. Conclusions: These findings suggest that even brief art-making interventions can be beneficial for stressed caregivers of cancer patients. As experience with art-making increased the impact, repeated sessions may be even more useful. We recommend that oncology units have dedicated studio spaces with therapeutic support and different forms of art-making available to meet individual caregiver needs. Highlights: Family and professional caregivers of cancer patients felt relaxed by art-making. Both art therapy and coloring improved affect, creative agency and self-efficacy. Both art therapy and coloring decreased anxiety, perceived stress, and burnout. Caregivers described enjoyment, problem solving, a sense of flow, and insight.